The Influence of Status on Group Drinking by Young Adults: A Survey of Natural Drinking Groups on Their Way To and From Bars - Dumas, T.; Wells, S.; Flynn, A.; Lange, J.; Graham, Kathryn (Williams and Wilkins, 2014)
Background: Young people’s social standing among friends and peers has been linked to general levels of drinking and has been shown to influence others’ drinking. We extend previous research by examining young adults’ status within their natural-occurring drinking groups as a predictor of their subsequent alcohol consumption and encouragement of group members’ alcohol consumption during a night out at licensed drinking establishments, a salient context for heavy drinking and alcohol-related risk among young adults. Methods: We recruited same-sex young adult drinking groups (n = 104 groups; 63 all-male; average group size = 3.4 members; Mage = 21.86) on their way to drinking establishments to complete a survey—containing measures of member-nominated within-group status, likeability, and self-reported alcohol consumption—and a breathalyzer test. At the end of the evening, participants completed the same alcohol consumption measures and were asked to nominate group members who encouraged other members to drink that night. Results: Multilevel analysis revealed that higher-status members engaged in the most alcohol consumption (via both self-report and breathalyzer) but in heavier drinking groups only. Higher-status members also encouraged the most alcohol consumed by others, regardless of levels of group drinking. Further, even though being liked by one’s peers was positively related to intoxication that night, it did not account for the significant relationship between within-group status and drinking. Conclusions: Results suggest that peer-related prevention programs for young adults’ problem drinking may benefit from focusing on the structure and dynamic of young people’s drinking groups. Also, programs targeting peer norms may be more successful if they incorporate status-related issues.